Ocorrência e transmissão de Alternaria spp. em sementes de canola - Migliorini, Patricia (2014)
Seeds of Brassica napus L. var. oleifera Metzg. (canola) may transport pathogenic organisms that have the ability to affect seed quality and cause diseases at different stages of crop development. The objective of this study was to evaluate and identify the species of Alternaria spp. associated with seeds canola during the process of manufacture and storage and to evaluate the potential for transmission and pathogenicity. Experiments were conducted at the Plant Protection Department and Laboratory of Phytopathology, both in the Federal University of Santa Maria, Santa Maria - RS. Hybrid seeds from Hyola 401, Hyola 61 and Hyola 60 were used. Field experiments utilized a randomized blocks design, while lab experiments were based on completely randomized design. Plants were evaluated after the onset of seed maturation, at harvest and during storage. During this period, assessments of physical, physiological and sanitary quality of seeds were performed. Through the transmission test was checked for the occurrence of Alternaria spp. causing symptoms of "damping- off" the seedlings. Six isolates of the pathogen were obtained, which were inoculated on seeds to check the pathogenicity. The morphological identification was made by visual observation of Alternaria and genetic identification using sequenced genomic region of Elongation Factor - 1α. The results showed that the physiological maturation of canola seed occurs 58 days after full bloom. Ripening increased the levels of contamination of Alternaria spp. seeds and decreased during storage. The species A. brassicicola, A. japonica and A. Alternaria, that affected the physiological quality of seeds and canola, were pathogenic causing necrosis on his lap and seedling damping-off.